3n+1=-2n+9

Simple and best practice solution for 3n+1=-2n+9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3n+1=-2n+9 equation:



3n+1=-2n+9
We move all terms to the left:
3n+1-(-2n+9)=0
We get rid of parentheses
3n+2n-9+1=0
We add all the numbers together, and all the variables
5n-8=0
We move all terms containing n to the left, all other terms to the right
5n=8
n=8/5
n=1+3/5

See similar equations:

| 4=2y-10 | | (y-1)+(y-24)=180 | | 4u-u−3u+2u=4 | | -z=10z+9 | | y-1+y-24=180 | | 3x-6=8x-4 | | -3–4(13m-14)=-467 | | 7+10f=-7+5f+7f | | x+32=x+67 | | 2x-(3x-1)=5-4(1-x) | | 4u−u−3u+2u=4 | | y+44+y-24+y-1=180 | | b−10=10−2b+10 | | x+59=51+x | | 400=2l+60 | | -4(r+5)-10r=-188 | | 9p-2p=14 | | 400=2(l+60) | | x+40+43=180 | | 7k=6+8k | | x+63+76=180 | | -6b+2=10-5b | | -4(32x-12)=-15 | | x+72+73=180 | | -4+6r=5+5r | | x+65+72=180 | | x+81+63=180 | | (-2x-8/6+1)-3=4 | | x+90+43=180 | | 108=-12-4*(-5n+7) | | −4+6p+18+3p=9(p+1)+5 | | 10-4j=-10-9j |

Equations solver categories